2004
DOI: 10.1016/j.jconhyd.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Field investigation into unsaturated flow and transport in a fault: model analyses

Abstract: Results of a fault test performed in the unsaturated zone of Yucca Mountain, Nevada, were analyzed using a three-dimensional numerical model. The fault was represented as a vertical fracture and the surrounding rock was treated as a dual-continuum system in the model. Model calibration against the seepage and water travel velocity data suggests that the lithophysal cavities connected to fractures can considerably enhance the effective fracture porosity and therefore retard water flow in fractures. Comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…Laboratory experiments on rock-matrix cores and field tracer tests at a larger scale have been often employed to estimate this coefficient [e.g., Skagius and Neretnieks, 1986;Ohlsson and Neretnieks, 1995;Ohlsson et al, 2001;Reimus et al, 2003bl. It has been found that the lab-scale matrix diffusion coefficient may be orders of magnitude smaller than a field-scale value for the same geologic site, indicating that matrix diffusion in the field is enhanced in some way [e.g., Hodgkinson and Lever, 1983;Maloszewski and Zuber, 1993;Shapiro, 2001;Neretnieks, 2002;Liu et al, 2003Liu et al, , 2004aAndersson et al, 20041. The enhancement may also be related to the significant inconsistency between rock properties (e.g., fracture aperture and matrix porosity) estimated from field tracer tests and those measured directly or estimated from hydraulic tests [e.g., Novakowski et al, 19851.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments on rock-matrix cores and field tracer tests at a larger scale have been often employed to estimate this coefficient [e.g., Skagius and Neretnieks, 1986;Ohlsson and Neretnieks, 1995;Ohlsson et al, 2001;Reimus et al, 2003bl. It has been found that the lab-scale matrix diffusion coefficient may be orders of magnitude smaller than a field-scale value for the same geologic site, indicating that matrix diffusion in the field is enhanced in some way [e.g., Hodgkinson and Lever, 1983;Maloszewski and Zuber, 1993;Shapiro, 2001;Neretnieks, 2002;Liu et al, 2003Liu et al, , 2004aAndersson et al, 20041. The enhancement may also be related to the significant inconsistency between rock properties (e.g., fracture aperture and matrix porosity) estimated from field tracer tests and those measured directly or estimated from hydraulic tests [e.g., Novakowski et al, 19851.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, site-specific process models and smallscale infiltration experiments were performed at Yucca Mountain to investigate the movement of water and solutes through faults and fracture systems Liu et al, 2004) and seepage into underground openings (Figure 4-, Trautz and Wang, 2002;Cook et al, 2003;Finsterle et al, 2003;Ghezzehei et al, 2004). Flint et al (2000) provide a brief overview of the approaches used to estimate regional recharge in the Death Valley Region of the Mojave Desert, an arid area of the United States, encompassing Yucca Mountain.…”
Section: Infiltration and Recharge Evaluationmentioning
confidence: 99%
“…In recent years, interest has grown in investigating solute transport through fractured rock, driven by environmental concerns related to radionuclide transport in fractured formations (e.g., Liu et al 2003Liu et al , 2004aHu et al 2004;Reimus and Callahan 2007). Moreover, suitability evaluations for underground geological storage of high-level radioactive waste in fractured rock have generated renewed interest in investigations of tracer and radionuclide transport in a fractured geological system.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, while understanding fracture-matrix interaction has been the focus of investigation into flow and transport processes in fractured rock, matrix diffusion has been gradually recognized as one of the most important mechanisms that control radionuclide transport processes in fractured rock (e.g., Neretnieks 1980;Neretnieks et al 1982;Maloszewski and Zuber 1993;Liu et al 2004a). Even in the laboratory, fracture-matrix diffusion is also found to be dominant Sudicky et al 1985;Wu and Pruess 2000).…”
Section: Introductionmentioning
confidence: 99%